Psychometric validation of the PROQOL-HIV questionnaire, a new health-related quality of life instrument-specific to HIV disease - Martin Duracinsky (2018)
Objectives: This study reports the psychometric validation of a new HIV/AIDS-specific health-related quality of life (HRQL) questionnaire, the Patient Reported Outcomes Quality of Life-HIV. The instrument was developed simultaneously across Europe, North and South America, Africa, Asia, and Australia to assess multidimensional quality of life impairments in the era of highly active antiretroviral therapy. Method: A cross-sectional study was performed in 8 countries. The pilot 70-item questionnaire was co-administered with the HIV symptoms index, the EQ-5D and Medical Outcomes Study-HIV questionnaires. Demographic and biomedical data were collected. After item analysis and reduction, convergent discriminant concurrent validity and known-group validity were examined. Internal consistency and reliability scores were assessed using Cronbach alpha and intraclass correlation. Results: The final sample of 791 patients was composed of 64% males (median age: 41 years, HIV diagnosis = 5 years), 13.8% were treatment naive. Item reduction yielded a 43-item form surveying 8 dimensions and 1 global health item that showed good convergent and discriminant validity and reliability (98% scaling success; Cronbach alphas 0.77-0.89). Correlations with EQ-5D and Medical Outcomes Study-HIV complied with concurrent validity expectations; likewise, correlations against the number of self-reported symptoms and depression showed good support for criterion validity. A test-retest study on French patients (n = 34) showed temporal stability (intraclass correlation coefficient = 0.86). Significant and meaningful differences of HRQL scores between countries were found. Conclusions: The Patient Reported Outcomes Quality of Life-HIV questionnaire is a valid and reliable instrument for assessing HRQL specific to HIV disease in different cultures and healthcare systems. © 2012 Lippincott Williams &Wilkins.